Synthesis, characterization, and growth simulations of Cu–Pt bimetallic nanoclusters - Khanal, Subarna; Spitale, Ana; Bhattarai, Nabraj; Bahena, Daniel; Velázquez Salazar, J. Jesús; Mejía Rosales, Sergio; Mariscal, Marcelo M.; Yacamán, Miguel José (Beilstein-Institut zur Förderung der Chemischen Wissenschaften, 2014)
Highly monodispersed Cu–Pt bimetallic nanoclusters were synthesized by a facile synthesis approach. Analysis of transmission electron microscopy (TEM) and spherical aberration (Cs)-corrected scanning transmission electron microscopy (STEM) images shows that the average diameter of the Cu–Pt nanoclusters is 3.0 ± 1.0 nm. The high angle annular dark field (HAADF-STEM) images, intensity profiles, and energy dispersive X-ray spectroscopy (EDX) line scans, allowed us to study the distribution of Cu and Pt with atomistic resolution, finding that Pt is embedded randomly in the Cu lattice. A novel simulation method is applied to study the growth mechanism, which shows the formation of alloy structures in good agreement with the experimental evidence. The findings give insight into the formation mechanism of the nanosized Cu–Pt bimetallic catalysts.